Memory, trauma and identity: trajectories in the fellowship of narcotics anonymous - Silva, Rodolfo Ferreira da (Laboratório Editorial Faculdade de Ciências e Letras, 2019)
The purpose of this paper is to investigate how members of the fellowship of Narcotics Anonymous deal with the issue of memory, trauma and treatment. The trauma is re- signified, providing the reconstruction of the social identities of the members, through a process where the key to recovery, according to this vision, passes through the narrative and the feeling of belonging and identification with the group.